Schema Therapy and the use of Politeness Plural in Greek-speaking populations: a need for cultural adaptation or a quest for early maladaptive schemas/modes?. (15th January 2019) - Kolonia, Konstantina; Tsartsara, Eirini; Giakoumaki, Ourania
Abstract: This paper is clinical practice-based, and examines the Greek cultural linguistic schema of Politeness Plural in the application of the Schema Therapy mode model. The philosophical principles of Schema Therapy and the importance the model ascribes on creating a warm therapist–client relationship as a pre-requisite for schema healing are discussed. We further explore the need for the therapist to be culturally sensitive to the linguistic use of Politeness Plural in Greek-speaking populations. We are looking into the reasons of why, whilst culturally sensitive, a schema therapist needs to remain inquisitive of potential maladaptive and/or internalized dysfunctional coping mechanisms of inter-relating that are masked by the use of the Politeness Plural linguistic schema. The implications the cultural linguistic schema of Politeness Plural can have in the therapy outcome are considered. Specifically, we argue that holding on to the Politeness Plural cultural linguistic schema may reinforce emotional distancing and compromise schema healing. The authors identify the need for more research to further understand the issues that are raised in this article. Although the focus of the article is on Greek populations, the matters under consideration may be valuable to other cultures.